Environmentally Responsive Graphene Systems. Issue 11 (23rd December 2013) - Zhang, Jing; Song, Long; Zhang, Zhipan; Chen, Nan; Qu, Liangti
<x xml:space="preserve">Abstract</x> Graphene materials have been attracting significant research interest in the past few years, with the recent focuses on graphene‐based electronic devices and smart stimulus‐responsive systems that have a certain degree of automatism. Owing to its huge specific surface area, large room‐temperature electron mobility, excellent mechanical flexibility, exceptionally high thermal conductivity and environmental stability, graphene is identified as a beneficial additive or an effective responding component by itself to improve the conductivity, flexibility, mechanical strength and/or the overall responsive performance of smart systems. In this review article, we aim to present the recent advances in graphene systems that are of spontaneous responses to external stimulations, such as environmental variation in pH, temperature, electric current, light, moisture and even gas ambient. These smart stimulus‐responsive graphene systems are believed to have great theoretical and practical interests to a wide range of device applications including actuators, switches, robots, sensors, drug/gene deliveries, etc.